Pengaruh Gaya Kepemimpinan dan Komitmen Organisasi Terhadap Kinerja Karyawan Koperasi Karyawan Minyak Caltex di Rumbai Pekanbaru - Kartika Fitri Ardhini; Jumiati Sasmita; Restu Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research aims to find the influence of leadership and organisational comitment on simultaniuos and partially to employee performance in Koperasi Karyawan Minyak Caltex di Rumbai Pekanbaru. The samples are top manager, middle manager and staff amount of 45 people. Analysis was performed using the multiple regresion analysis on Koperasi Karyawan Minyak Caltex di Rumbai Pekanbaru. The result of this research are; there are significant influence of leadership and organisational comitment on simultaniuos to employee performance with p value 0.013 < 0.05, there are no significant influence of leadership partially to employee performance with p value 0.350> 0.05 and there are significant influence of organisational comitment on partially to employee performance with p value 0.006 < 0.05. Adjusted R Square is 0.148 or 14.8%, employee performance are explained by leadership and organisational comitment and the are percentage the rest by another factors.Keywords : leadership style and organisational commitment and employee performance